ANALISIS MINAT DAN PEMANFAATAN APLIKASI BERBASIS FINANCIAL TECHNOLOGY (FINTECH) PADA KARYAWAN BANK PEMBIAYAAN RAKYAT SYARIAH AMANAH UMMAH, KABUPATEN BOGOR, JAWA BARAT - Riyadi, Fariz Fajar; Trihantana, Rully; Kusumaningrum, Ria (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
The presence of application-based Financial Technology (Fintech) Payment services is an innovation that makes it one of the supports in non-cash transactions and supports the National Non-Cash Movement (GNNT) which has been launched by Bank Indonesia (BI) since 2014. Fintech Payment has a portion greater usage than other Financial Technology services. The use of these services has increased during the COVID-19 pandemic because it can reduce physical contact between buyers and sellers during transactions. In 2021 the use of the DANA, OVO and GOPAY applications will be the highest used fintech payment applications and have the largest users on the island of Java, namely Jakarta, West Java, Central Java, Yogyakarta and East Java. Therefore an analysis is needed regarding the interest and utilization of financial technology-based applications. This research was conducted with the aim of knowing the factors and perceptions of BPRS Amanah Ummah employees about their interest in using the application. This research uses quantitative survey method. The technique used in collecting data by distributing questionnaires. The results of this study indicate that Perceived Convenience (X1), Perceived Usefulness (X2), and Perceived Trust (X3) influence the interest in using financial technology (fintech)-based applications (Y) by 70.1%. Meanwhile, the rest (29.9%) is influenced by other variables outside of this study. Perceived trust has a significant effect on interest in using financial technology (fintech)-based applications, while perceived convenience and perceived usefulness have no significant effect. So that if there is an increase or decrease in the level of trust in fintech payment services, this will be followed by an increase or decrease in interest in using fintech payments (DANA/OVO/GOPAY)..